Gifted high school students, research on their creativity - Aris Redó, Nuria; Millán Gutiérrez, María Ángeles (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Creativity, a construct that has been raised from different perspectives throughout history and is defined, measred and interpreted by different authors. This article aisms to study how creativity Works in fifted students. To do this, two instruments are applied, two test, which are contrasted, to analyze the dimensions of creativity to a sample of secondary school students. The results show differences in favor of students with high ability. The conclusions are that it allows establishing a significant relationship between creativity and gifted students.